Innate immunity to S. aureus: evolving paradigms in soft tissue and invasive infections - Brandt, Stephanie L. (J Immunol, 2018)
Staphylococcus aureus causes a wide range of diseases that together embody a significant public health burden. Aided by metabolic flexibility and a large virulence repertoire, S. aureus has the remarkable ability to hematogenously disseminate and infect various tissues, including skin, lung, heart, and bone, among others. The hallmark lesions of invasive staphylococcal infections, abscesses, simultaneously denote the powerful innate immune responses to tissue invasion, as well as the ability of staphylococci to persist within these lesions. In this manuscript, we review the innate immune responses to S. aureus during infection of skin and bone, which serve as paradigms for soft tissue and bone disease, respectively.